Case Report: Chemotherapy-free treatment with camrelizumab and anlotinib for elderly patients with KRAS and TP53 mutated advanced lung cancer - Wenbo Qi; Wenbo Qi; Wenbo Qi; Dayong Xi; Dayong Xi; Dayong Xi; Yuping Bai; Yuping Bai; Yuping Bai; Le Liu; Le Liu; Le Liu; et al. (Frontiers Media S.A., 2023)
Background: Lung cancer is a major public health issue and an enormous burden on society in China. Most lung cancers occur in elderly patients with non-small cell lung cancer (NSCLC), and many factors limit their treatment options. Chemotherapy-free therapy can avoid psychological fear, treatment pain, and adverse reactions caused by chemotherapy. Patients with non-small cell lung cancer with tumour protein p53 (TP53) gene mutations or Kirsten rat sarcoma viral oncogene homologue (KRAS) gene mutations tend to be more sensitive to anlotinib or programmed cell death protein 1 (PD-1) drugs. However, Kirsten rat sarcoma viral oncogene homologue is a proto-oncogene downstream of the epidermal growth factor receptor (EGFR) gene; therefore, if the Kirsten rat sarcoma viral oncogene homologue gene has an activating mutation, EGFR-targeted drug resistance may occur. Further studies are needed to explore whether patients with dual Kirsten rat sarcoma viral oncogene homologue and tumour protein p53 mutations can be treated with targeted immunotherapy without chemotherapy.Case presentation: A 74-year-old man was referred to the Lanzhou University Second Hospital due to chest tightness, shortness of breath, and weight loss for 2 months and was diagnosed with moderately to poorly differentiated adenocarcinoma. Laboratory examinations showed increased alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), cancer antigen (CA)-125, and CA199 levels, and gene sequencing indicated mutations in Kirsten rat sarcoma viral oncogene homologue and tumour protein p53. Immunohistochemical analysis showed positive PD-L1 and PD-1 expression. Peripheral blood immune checkpoint test using flow cytometry indicated that the PD-1 + CD8 levels were positive. After multi-disciplinary treatment, therapy with a combination of anlotinib and camrelizumab was initiated. Camrelizumab 200 mg was administered intravenously once every 3 weeks. Anlotinib 12 mg was administered orally daily before breakfast for 2 weeks with a week of rest in every cycle of 21 days. A reduction in alpha-fetoprotein, carcinoembryonic antigen, CA125, CA199, and CA724 levels was observed up to the first cycle, which decreased within the normal limits up to the second cycle and continued until the eighteenth cycle. The patient's chest tightness, shortness of breath, weight loss, and other symptoms significantly improved following treatment. Computed tomography imaging showed that the neoplastic lesion was dramatically reduced. The patient is currently being followed-up for more than 2 years to evaluate the duration of the response.Conclusion: Chemotherapy-free immunotherapy combined with targeted therapy is an effective treatment for advanced non-small cell lung cancer in elderly patients with Kirsten rat sarcoma viral oncogene homologue and tumour protein p53 mutations. Such therapies should be supported with further clinical studies with larger sample sizes.